Evaluation of production reserves use efficiency as a basis for taking perfected management solutions on PJSC «Poltava Automobile Unit Plant» (Economics and region, 2019)
The urgency of the article is due to the need to address issues related to the establishment of effective use of industrial stocks at the enterprise. Industrial stocks take part in the main activity, without their participation in the management process, the full functioning of an industrial enterprise is impossible. The purpose of this study is to determine the effectiveness of the use of industrial stocks at PJSC "Poltava Automobile Unit Plant" and to develop proposals for their optimization at the investigated enterprise. The methodological basis of the research is the system-structural approach, which involves consideration of the object as a holistic, multidimensional and multilevel system. In the process of research, the following methods were used: theoretical generalization, statistical analysis – for studying, grouping and comparing empirical data in order to study the trends of changes in inventories in dynamics. In the course of the analysis, it was established that the availability and condition of industrial stocks in the enterprise have a greater positive effect on its activities, which also testifies to the good economic efficiency of their use. To increase the efficiency of using this type of enterprise resources, it is necessary to analyze trends in the changes in the components of production stocks. The elements of the scientific novelty of the results are to substantiate the organizational, theoretical and methodological provisions and provide practical recommendations for the effective use of production resources at PJSC "Poltava Automobile Unit Plant", which will improve its effectiveness of management of industrial stocks of the enterprise. The practical significance of the results obtained is that the implementation of the conclusions and proposals provided will contribute to the efficient use of inventories. The results of the conducted research can be used in the process of improving the system of control of inventory at the enterprise of PJSC "Poltava Automobile Unit Plant".
Keywords: production stocks; current assets; fixing ratio; rotation; turnover duration; material concentration; material productivity; profitability